ANALISIS OPPORTUNITY COST BIOKONVERSI SAMPAH ORGANIK MENGGUNAKAN MAGGOT BSF (BLACK SOLDIER FLY) - Lilik Ambarwati; Prafidhya Dwi Yulianto (Sekolah Tinggi Ilmu Ekonomi Semarang, 2023)
This study aims to determine the opportunity cost of processing waste using BSF maggot compared to the monthly waste costs incurred by residents, as well as evaluating residents' decisions in choosing the current waste processing costs. Descriptive analysis is used in this study, intended to provide a clear description and description of opportunity cost analysis in waste management decision making. The Sorosutan Village of Yogyakarta became the object of research, with the result that waste management using BSF maggot saved costs of Rp. 3,331,000 for 108 residents, compared to when residents used cart services with a monthly fee of Rp. 30,000 per head of family. So that the selection of waste management methods carried out by residents is currently not appropriate.